Integrating fuzzy-MCDM methods to select project portfolios under uncertainty: the case of a pharmaceutical company - Souza, Guilherme Martins de (2022)
Goal: The present work aims to improve the project portfolio selection processes under uncertainty of pharmaceutical companies by integrating two Multicriteria Decision Making (MCDM) methods in a fuzzy environment: the AHP and the VIKOR methods. Design / Methodology / Approach: We employed normative axiomatic modeling as the methodology for our work. The MCDM are subjective methods representing decision-makers preferences and assisting the project portfolio selection process. Thus, the model is founded on integrating the fuzzy-AHP and fuzzy-VIKOR methods; the first one determines the importance of the company's strategy and the second for elaborating the project ranking. We validated this methodology in a Brazilian subsidiary of one of the biggest pharmaceutical enterprises worldwide. Results: The developed model considers the evaluators' scores' indecision, enhancing the project portfolio selection process and optimizing its decision-making. Limitations of the investigation: The proposed method does not verify the correlation, interdependence, or cannibalization between the criteria and the projects, which are common limitations to MCDM subjective approaches. In addition, resource constraints are not considered and scheduling routines. Practical implications: The pharmaceutical market is heated by the increase in life expectancy, greater access to medications, and the most recurrent disease outbreaks, resulting in greater competitiveness, increasing the need for companies to seek greater strategic projects selection efficiency. Originality / Value: A well-structured and assertive project portfolio selection becomes extremely important for the pharmaceutical market to keep the company competitive in the market, which explains the importance of this work.